Comparison of computed Tomography and ultrasonography in evaluating causes of obstructive jaundice - Lovely Kaushal; Abhijit Patil; Chandra Prakash Ahirwar; Kshitij Sharma (International Journal of Medical Research and Review, 2016)
Objective: To observe and compare the role of ultrasonography and computed tomography in evaluation of causes of obstructive jaundice.Materials and Methods: A total of 100 patients were enrolled in this cross-sectional study done in Department of Radiodiagnosis and Imaging, Gandhi Medical College, Bhopal.Results: Computed tomography and ultrasonography were able to detect the presence of biliary obstruction in 100% of cases. Liver function tests were altered in all the patients with alkaline phosphatase raise out of proportion to the AST/ALT. The highest incidence of biliary obstruction was found in 61-70 years’ age group with mean (±SD) age of the patient was 62.7 ± 12.64 years. Sensitivity, specificity and accuracy of computed tomography and ultrasonograhy in detecting the various causes of obstructive jaundice were 90.85%, 99.21% ,98.15% and 84.15%, 98.86% and 97% respectively.Conclusions: Computed tomography has a high sensitivity, specificity and accuracy in detecting the causes of biliary obstruction. Considering these attributes, computed tomography can be used as an effective diagnostic modality in cases of obstructive jaundice. Accuracy and specificity for ultrasonography is high in detecting the causes of biliary obstruction with a slightly low sensitivity. Hence, ultrasonography can be used as an effective screening modality in cases of obstructive jaundice.